Implementasi Program Merdeka Belajar-Kampus Merdeka di SD Negeri 07 Balingka - Ratna Rosima Wulandari; Azwar Ananda; Hasrul Piliang; Junaidi Indrawadi (Jurusan Ilmu Sosial Politik, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2023)
This article aims to describe the implementation of the Teaching Campus Program Batch 1 Merdeka Belajar – Kampus Merdeka (MBKM) at SD Negeri 07 Balingka. The type of research used in this research is descriptive qualitative. The determination of informants in this study used a purposive sampling technique using data collection techniques including observation, interviews and documentation studies. Test the validity of the data in this study using data triangulation techniques. The data obtained were analyzed using data analysis techniques including data collection, data reduction, data presentation and drawing conclusions. The results showed that in the implementation of the Kamous Mengajar program Batch 1 at SD Negeri 07 Balingka there were stages in implementing the teaching campus namely the coordination stage, the observation stage, the planning stage, the activity program implementation stage and the reporting stage. In implementation, there are program activities including academic application, administrative application, application of technology adaptation and non-academic application. he reporting stage employed assessment instruments such as self-assessment, field supervisor assessment, teacher assessment, and peer assessment. During implementation there are supporting factors, namely good and clear communication, coordination and socialization. Meanwhile, the obstacles starting from the coordination stage to the reporting stage were lecture schedules that collided with campus teaching and the MBKM system had errors. The limitation of this study is that it does not show the inhibiting factors from the school side.